2022
DOI: 10.7759/cureus.22343
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Intestinal Schwannoma in a Patient of Ulcerative Colitis With Adhesive Intestinal Obstruction: A Case Report

Abstract: Gastrointestinal (GI) schwannomas are very rare. Among GI schwannoma, the most common site is the stomach. Very few cases of intestinal schwannoma have been reported in the literature. Moreover, intestinal schwannoma in the setting of inflammatory bowel disease has rarely been reported. We report a case of ileal schwannoma incidentally detected in a 52-year-old lady with long-lasting ulcerative colitis having intestinal obstruction. On laparotomy, the patient was found to have adhesive intestinal obstruction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Our patient had follow-ups within 4 years in the surgical outpatient clinic every 6 months and remains symptom-free. Literature data also supports the idea that GI schwannoma is a benign condition and nearly no malignant transformation is observed [2,7,[12][13][14][15], and the long-term follow-ups of patients with schwannomas of the gastrointestinal tract have not shown any propensity to recurrence following complete excision [2].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our patient had follow-ups within 4 years in the surgical outpatient clinic every 6 months and remains symptom-free. Literature data also supports the idea that GI schwannoma is a benign condition and nearly no malignant transformation is observed [2,7,[12][13][14][15], and the long-term follow-ups of patients with schwannomas of the gastrointestinal tract have not shown any propensity to recurrence following complete excision [2].…”
Section: Discussionsupporting
confidence: 58%
“…Since the findings of small bowel schwannomas are extremely rare, their incidence in the population is unclear and has only been estimated in some existing studies [2,7]. In the current digital literature, we found that only a few small bowel schwannomas have been described [2,7,[12][13][14][15][16][17][18][19][20][21][22] that localised to the duodenum, jejunum, or ileum. The majority of patients (about 2/3) were females.…”
Section: Discussionmentioning
confidence: 74%